Hierarchical patterning modes orchestrate hair follicle morphogenesis - Glover, James D; Wells, Kirsty L; Matthäus, Franziska; Painter, Kevin J; Ho, William; Riddell, Jon; Johansson, Jeanette A; Ford, Matthew J; Jahoda, Colin A B; Klika, Vaclav; Mort, Richard L; Headon, Denis J (PLoS biology, 2017)
Two theories address the origin of repeating patterns, such as hair follicles, limb digits, and intestinal villi, during development. The Turing reaction-diffusion system posits that interacting diffusible signals produced by static cells first define a prepattern that then induces cell rearrangements to produce an anatomical structure. The second theory, that of mesenchymal self-organisation, proposes that mobile cells can form periodic patterns of cell aggregates directly, without reference to any prepattern. Early hair follicle development is characterised by the rapid appearance of periodic arrangements of altered gene expression in the epidermis and prominent clustering of the adjacent dermal mesenchymal cells. We assess the contributions and interplay between reaction-diffusion and mesenchymal self-organisation processes in hair follicle patterning, identifying a network of fibroblast growth factor (FGF), wingless-related integration site (WNT), and bone morphogenetic protein (BMP) signalling interactions capable of spontaneously producing a periodic pattern. Using time-lapse imaging, we find that mesenchymal cell condensation at hair follicles is locally directed by an epidermal prepattern. However, imposing this prepattern's condition of high FGF and low BMP activity across the entire skin reveals a latent dermal capacity to undergo spatially patterned self-organisation in the absence of epithelial direction. This mesenchymal self-organisation relies on restricted transforming growth factor (TGF) β signalling, which serves to drive chemotactic mesenchymal patterning when reaction-diffusion patterning is suppressed, but, in normal conditions, facilitates cell movement to locally prepatterned sources of FGF. This work illustrates a hierarchy of periodic patterning modes operating in organogenesis.
Keywords: buněčná diferenciace; signální transdukce; Signal Transduction; Female; kůže; zvířata; myši; Mice; Hair Follicle; rozvržení tělního plánu; ženské pohlaví; Male; Body Patterning; transformující růstový faktor beta; Cell Differentiation; stanovení celkové genové exprese; Transforming Growth Factor beta; Mice, Inbred Strains; vlasový folikul; Animals; Gene Expression Profiling; mužské pohlaví; inbrední kmeny myší; Skin